2011
DOI: 10.1128/aem.06136-11
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Improved Cell Yield and Increased Specific Productivity Enhances Recombinant Enzyme Production in Genome-Reduced Bacillus subtilis Strain MGB874

Abstract: Genome reduction strategies to create genetically improved cellular biosynthesis machineries for proteins and other products have been pursued by use of a wide range of bacteria. We reported previously that the novel Bacillus subtilis strain MGB874, which was derived from strain 168 and has a total genomic deletion of 874 kb (20.7%), exhibits enhanced production of recombinant enzymes. However, it was not clear how the genomic reduction resulted in elevated enzyme production. Here we report that deletion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 56 publications
2
54
0
2
Order By: Relevance
“…This is not unusual, as described for B. subtilis, where not the genome reduction by 20% in general but mainly the deletion of the rocDEF-rocR region was shown to be responsible for an elevated protein production. This region is involved in arginine degradation, and the deletion causes drastic changes in glutamate metabolism, leading to improved cell yields (45). In the case of C. glutamicum, the relevant operon codes for an RM system first described in the late 1980s (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…This is not unusual, as described for B. subtilis, where not the genome reduction by 20% in general but mainly the deletion of the rocDEF-rocR region was shown to be responsible for an elevated protein production. This region is involved in arginine degradation, and the deletion causes drastic changes in glutamate metabolism, leading to improved cell yields (45). In the case of C. glutamicum, the relevant operon codes for an RM system first described in the late 1980s (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of this genomic region significantly increased the production of cellulase Egl-237 and M-protease [7,8], with subsequent analyses revealing that deletion of the rocDEF-rocR region was responsible for the enhanced enzyme production [11]. However, here, we found that deletion of the rocDEF-rocR region caused a significant decrease in the production level of AmyK38 (Additional file 1: Figure S1).…”
Section: Resultsmentioning
confidence: 72%
“…Enlightened by that, we attempted to enhance intracellular glutamate synthesis by genetically modifying related genes. Deletion of RocR (a regulator participating in glutamate degradation by activating the gene encoding glutamate dehydrogenase, rocG) was found to increase the flux from 2-oxoglutarate to glutamate, and then lead to increased synthesis of the other amino acids via transamination in B. subtilis 168 [13]. Besides rocR, rocG, gudB and odhA were also targeted in this study.…”
Section: Discussionmentioning
confidence: 96%